PERAN JOGED DANYANG DALAM RITUAL BERSIH DESA DI DUSUN NATAH - Siti Khasanah; Katarina Indah Sulastuti (Institut Seni Indonesia Surakarta, 2019)
Joged Danyang is the core dance in the village’s clean ritual ceremony held in Natah hamlet of Tirtomoyo district Wonogiri. Natah villagers believe that Natah Hamlet is guarded by Danyang named Gadhung Mlathi. People believe that if not implementing a clean ritual village then there will be catastrophe. The problems that will be discussed in this research are roles and forms. The method used is a qualitative method with a descriptive analytical approach displays the observation results based on the actual circumstances. A discussion on the form of Joged Danyang using the theory of Suzane K. Langer includes: Dancers, motion, makeup, dance music, time and place, and offerings. To discuss the role of Joged Danyang using the theory of Sumandiyo Hadi as worship or adoration to the spirit of ancestors and communication with God or the Almighty, as a means of influencing the power of nature and as a means for legitimacy. Results of this study showed that the form of a Joged Danyang very simple, movement experiencing repetition and view of dancers focus on Danyang furniture. Joged Danyang role respect and communication to the community. Joged Danyang from the clean ritual of the village. Some impacts of entertainment, economic aspects, and aspects of the Social. Thus Joged Danyang has an important role in Natah community of Tirtomoyo Sub-district and surrounding areas.Keywords: Joged Danyang, form, and role.